Nanoparticle-based assays in automated flow systems: A review - Marieta L C Passos (2015)
Nanoparticles (NPs) exhibit a number of distinctive and entrancing properties that explain their ever increasing application in analytical chemistry, mainly as chemosensors, signaling tags, catalysts, analytical signal enhancers, reactive species generators, analyte recognition and scavenging/separation entities. The prospect of associating NPs with automated flow-based analytical is undoubtedly a challenging perspective as it would permit confined, cost-effective and reliable analysis, within a shorter timeframe, while exploiting the features of NPs. This article aims at examining state-of-the-art on continuous flow analysis and microfluidic approaches involving NPs such as noble metals (gold and silver), magnetic materials, carbon, silica or quantum dots. Emphasis is devoted to NP format, main practical achievements and fields of application. In this context, the functionalization of NPs with distinct chemical species and ligands is debated in what concerns the motivations and strengths of developed approaches. The utilization of NPs to improve detector's performance in electrochemical application is out of the scope of this review. The works discussed in this review were published in the period of time comprised between the years 2000 and 2013.